2019
DOI: 10.1021/acs.nanolett.9b03396
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Electron and Hole Transport Dynamics in Halide Perovskite Nanowires

Abstract: For optoelectronic devices, high transport mobilities of electrons and holes are desirable, which, moreover, should be close to identical. Acousto-optoelectric spectroscopy is employed to probe the spatiotemporal dynamics of both electrons and holes inside CsPbI3 nanowires. These dynamics are induced without the need for electrical contacts simply by the piezoelectric field of a surface acoustic wave. Its radio frequency of fSAW = 324 MHz natively avoids spurious contributions from ion migration typically occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The mobility value found here is in good agreement with values reported in literature, [ 36,38,39 ] although differs from others. [ 17,40 ] We note that differences in crystallinity and composition (i.e., exchanging halide species), as well as measurement schemes, could alter the mobility values. Simulation curves for different values of μ are shown in Note VI, Supporting Information and illustrate the close relationship between the delayed PL “hump” and carrier diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…The mobility value found here is in good agreement with values reported in literature, [ 36,38,39 ] although differs from others. [ 17,40 ] We note that differences in crystallinity and composition (i.e., exchanging halide species), as well as measurement schemes, could alter the mobility values. Simulation curves for different values of μ are shown in Note VI, Supporting Information and illustrate the close relationship between the delayed PL “hump” and carrier diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] In other CsPbBr 3 systems higher FET mobilities with record values of up to 2.2 cm 2 V −1 s −1 at room temperature have been reported. [ 12,28,29,39 ] However, even these record mobilities are still at well below what has been expected from time‐resolved photoluminescence measurements, [ 7,40 ] acousto–optoelectronic spectroscopy, [ 41 ] Hall‐effect measurements, [ 36,42 ] and THz spectroscopy. [ 43 ] Thus, a better understanding of the underlying transport mechanisms bears great potential for optimizing mobilities of all‐inorganic perovskite devices.…”
Section: Resultsmentioning
confidence: 99%
“…While as bulk crystal they are discussed as solar cell material, [174] nanowires have already been interfaced with SAWs utilizing the strain mediated charge transport. [175] Studies have also shown that perovskite nanocrystals show single photon emission and therefore act as artificial atoms. [176,177] The detection of acoustic phonon sidebands [178] makes them also promising candidates for active remote phonon control.…”
Section: Artificial Atoms In Layered Materialsmentioning
confidence: 99%